2023
DOI: 10.1371/journal.pone.0281610
|View full text |Cite
|
Sign up to set email alerts
|

Hippo signaling and histone methylation control cardiomyocyte cell cycle re-entry through distinct transcriptional pathways

Abstract: Aims Accumulating data demonstrates that new adult cardiomyocytes (CMs) are generated throughout life from pre-existing CMs, although the absolute magnitude of CM self-renewal is very low. Modifying epigenetic histone modifications or activating the Hippo-Yap pathway have been shown to promote adult CM cycling and proliferation. Whether these interventions work through common pathways or act independently is unknown. For the first time we have determined whether lysine demethylase 4D (KDM4D)-mediated CM-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 111 publications
(162 reference statements)
1
3
0
Order By: Relevance
“…In addition, the protein expression of CCND1 and PCNA also confirmed the above results. Previously, there was evidence which demonstrated that Kdm4d could regulate adult cardiomyocyte cycling and proliferation by activating different cell cycle regulators [31], consistent with our present results. These findings, and our results, indicate that the dysregulation of Kdm4d affects cell proliferation and the cell cycle.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the protein expression of CCND1 and PCNA also confirmed the above results. Previously, there was evidence which demonstrated that Kdm4d could regulate adult cardiomyocyte cycling and proliferation by activating different cell cycle regulators [31], consistent with our present results. These findings, and our results, indicate that the dysregulation of Kdm4d affects cell proliferation and the cell cycle.…”
Section: Discussionsupporting
confidence: 93%
“…81 The nuclear transportation and activation of YAP/TAZ can cause histone acetylation by the related lysine acetyltransferases CBP and p300. 82 Despite the fact that HIPPO pathway or YAP mediated alterations in chromatin accessibility have received great attention in recent studies, 83,84 it remains unclear whether active YAP can facilitate histone modifications at specific differentiation gene promoters in response to topographical or mechanical cues. 85−87 Here, we hypothesize that YAP, together with other nuclear proteins, may regulate histone modification and expression of differentiation related genes in the mechanotransduction processes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Despite the fact that HIPPO pathway or YAP mediated alterations in chromatin accessibility have received great attention in recent studies, , it remains unclear whether active YAP can facilitate histone modifications at specific differentiation gene promoters in response to topographical or mechanical cues. …”
Section: Resultsmentioning
confidence: 99%
“…We also postulate that some genes conserved for various stage of cell functions in different cell types have multiple regulatory mechanisms to fine tune gene expression, such as by microRNA, 9 and epigenetic histone modifications. 20,21 It is worth noting that Cdk1 itself can affect histone epigenetic landscape as shown in mouse embryonic stem cells. 22 The GMR reporter system can be used with both live cell reporters to decipher the intricate cellular processes such as lineage 13 specification and tracking (e.g., cardiomyocyte) and phenotype (e.g., myocyte maturity or cell cycle/proliferation activities) and functions (e.g., myocyte electrical and contractile activities).…”
Section: Discussionmentioning
confidence: 99%